Deep : freediving, renegade science, and what the ocean tells us about ourselves - Nestor, James (Houghton Mifflin Harcourt, 2014)
"While on assignment in Greece, journalist James Nestor witnessed something that confounded him: a man diving 300 feet below the ocean's surface on a single breath of air and returning four minutes later, unharmed and smiling. This man was a freediver, and his amphibious abilities inspired Nestor to seek out the secrets of this little-known discipline. In Deep, Nestor embeds with a gang of extreme athletes and renegade researchers who are transforming not only our knowledge of the planet and its creatures, but also our understanding of the human body and mind. Along the way, he takes us from the surface to the Atlantic's greatest depths, some 28,000 feet below sea level. He finds whales that communicate with other whales hundreds of miles away, sharks that swim in unerringly straight lines through pitch-black waters, and seals who dive to depths below 2,400 feet for up to eighty minutes--deeper and longer than scientists ever thought possible. As strange as these phenomena are, they are reflections of our own species' remarkable, and often hidden, potential--including echolocation, directional sense, and the profound physiological changes we undergo when underwater. Most illuminating of all, Nestor unlocks his own freediving skills as he communes with the pioneers who are expanding our definition of what is possible in the natural world, and in ourselves"--